Ladybug girl at the beach ebook - Soman, David (Ladybug Girl., 2010)
It is preschooler Lulu’s first time at the beach and she needs to conquer her fear of the ocean in this hardcover picture book from the New York Times bestselling Ladybug Girl series.   Lulu has never been to the beach but she knows she is going to love it…until she sees just how big and loud the ocean is. She and her dog Bingo decide that they will make sandcastles, fly kites, and get ice cream instead of swimming. But then the ocean waves snatch Lulu’s favorite pail. This is a job for Ladybug Girl! When Lulu is Ladybug Girl, she is brave and nothing can stop her from rescuing her pail – and suddenly she is in the ocean and it is fun!   This story is the perfect preparation for a first beach vacation, or to explore a new experience with a preschooler. Mama and Papa are never far away while Ladybug Girl builds up her courage and confronts something scary for the first time.   For fans of Fancy Nancy and Angelina Ballerina, the Ladybug Girl series honors courage, creativity, and a love of nature!